Character Education and Entrepreneurship in the Young Generation: A Case Study Of Vanilla Cultivation in Letkole Village - Griselda, Giovani Griselda Henukh; D Bani, Marsi; Kollo, Fredik Lambertus (Jurnal Edukasi Terkini, 2025)
Purpose – Character education and entrepreneurship are important components in creating a generation that is resilient and able to compete in the global world. The young generation has an important role, one of which is in the development of agriculture in Indonesia, agriculture can be a forum for character development which can later influence the formation of the personality of young citizens. The purpose of this study is to examine how the vanilla cultivation process can be used as a medium for character and entrepreneurship education in the young generation in Letkole Village. Methodology/Design/Approach – In this study, the researcher uses 5 sources that enter the age, namely 19-24 years old, to later conduct a deeper study related to the material to be researched, this study uses qualitative methods, namely documentation, observation, and interviews as sources of data acquisition. Findings – The results of this study show that vanilla cultivation not only provides economic benefits but also functions as an effective medium for character education and entrepreneurship in the younger generation.